2021
DOI: 10.33963/kp.a2021.0035
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical follow-up of the resorbable magnesium scaffolds in acute coronary syndrome patients

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.Long-term clinical follow-up of the resorbable magnesium scaffolds in acute coronary syndrome patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In the contrast, the data on implantation of Magmaris in ACS conditions are more comprehensive and reliable. Several observational registries confirmed favorable short-term and long-term outcomes [ 6 , 29 ] Furthermore, recently published data from the largest all-comers Magmaris registry [ 30 ] which included 2054 subjects showed that the one-year TLF rate was 4.3% with only one subacute in-stent thrombosis event. The results obtained are far more favorable than the first generation of BRS and comparable to the newest DES.…”
Section: Discussionmentioning
confidence: 99%
“…In the contrast, the data on implantation of Magmaris in ACS conditions are more comprehensive and reliable. Several observational registries confirmed favorable short-term and long-term outcomes [ 6 , 29 ] Furthermore, recently published data from the largest all-comers Magmaris registry [ 30 ] which included 2054 subjects showed that the one-year TLF rate was 4.3% with only one subacute in-stent thrombosis event. The results obtained are far more favorable than the first generation of BRS and comparable to the newest DES.…”
Section: Discussionmentioning
confidence: 99%
“…Observed in our study cohort favorable clinical outcomes (no significant differences in terms of Primary outcome, principally secondary outcome, TLF, with additional lack of stent thrombosis in the study population) after Magmaris implantation in diabetic ACS-NSTE population seems to support data obtained in all-comers Magmaris registries. [48][49][50][51] Despite no statistically significant difference in terms of study endpoints occur noticeable unfavorable trend in restenosis ratio in DM t.2 subpopulations occurred (8.1% vs 3.3%; p = 0.182). Additionally taking into consideration unfavorable long-term outcomes of first-generation BRS (Absorb) 41,52 future long-term high-number studies are required for a proper evaluation of Magmaris performance in the diabetic population.…”
Section: Discussionmentioning
confidence: 86%
“…This trend, was remarked upon in a study comparing Magmaris to Orsiro (second generation of DES) [ 34 ], was statistically irrelevant. Furthermore, a recently published study suggests favorable safety features and long-term prognosis of patients treated with Magmaris scaffold implanted in terms of ACS [ 35 , 36 ]. Such a good clinical performance of the magnesium BRS was achieved by overcoming the scaffold thrombosis issues.…”
Section: Discussionmentioning
confidence: 99%